Seasonality and sources of light-absorbing aerosols at Summit, Greenland - Hu, Jason (Georgia Institute of Technology, 2015)
The Greenland ice sheet (GIS) is a key component of the warming Arctic climate, having the potential to dramatically influence sea level through melting. Light-absorbing aerosols are thought to be significant contributors to warming in the Arctic, because of their effect on the radiation balance through both aerosol absorption in the atmosphere as well as absorption in surface snow after particulate deposition. At this time it is not possible to estimate the impact of aerosol absorption on the radiation balance over Greenland due to the lack of in-situ measurements. Here, we present time series and estimates of key aerosol optical properties in order to better understand the seasonality and sources of aerosols over central Greenland, and compare their values with other Arctic sites. In-situ measurements made at Summit, Greenland from May 8, 2011 to December 31, 2014 include aerosol light absorption coefficient (σap) and light scattering coefficient (σsp); calculated parameters include absorption Ångström exponent (AAE), and single scattering albedo (ωo). The light absorption and scattering coefficients were found to be low in the winter and highest in the spring and summer. Spring-summer means of σap and σsp were 0.15 ± 0.15 Mm-1 and 2.35 ± 2.80 Mm-1, respectively. Mean AAE was 0.97 ± 0.29 in the spring and summer, indicating that black carbon (BC), and not dust and/or organic brown carbon (BrC), is the main aerosol light absorber. Mean ωo was 0.93 ± 0.03, which is similar to values measured at Barrow, Alaska, USA (0.94 ± 0.05) and Ny-Ålesund, Svalbard, Norway (0.95 ± 0.06). Summit exhibits ωo as low as Barrow and Ny-Ålesund although it is an isolated high-altitude site indicating the importance of aerosol light absorption over the most remote Arctic locations. M.S.